First generation diagnostic assay to differentiate viral and bacterial infections in pigs - CGIAR Research Program on Livestock (2021)
Development of a 3-transcript host expression assay to differentiate between viral and bacterial infections in pigs. Ready for next steps in optimizing the assay.